2021
DOI: 10.1530/ec-21-0277
|View full text |Cite
|
Sign up to set email alerts
|

Hypogonadism in Prader–Willi syndrome from birth to adulthood: a 28-year experience in a single centre

Abstract: Background: Hypogonadism is a key feature of Prader-Willi syndrome (PWS) but clear strategies for hormone replacement are lacking. Objective: To evaluate gonadal status and outcome in patients attending a Scottish PWS clinic from 1991-2019. Methods: In 93 (35F:56M) patients, median follow-up 11.2 years, gonadal and pubertal status were assessed clinically. Pelvic ultrasound findings and basal/stimulated gonadotrophins were compared with age-matched controls. Results: Females: Of 22 patients aged >11, 9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Increasing behavioral disturbance was noted in one of eight individuals following testosterone treatment. Similarly, 4 of 24 individuals ceased testosterone treatment due to increasing behavioral disturbance in a recent analysis in people with PWS (Kherra et al, 2021), whereas another analysis reported behavioral disturbance in one-third of individuals (Pellikaan et al, 2021). Few behavioral problems were attributed to testosterone treatment in a questionnaire of practitioners experienced in care of individuals with PWS (Eiholzer et al, 2021), and are not commonly reported in the literature following initiation of testosterone treatment (Noordam et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing behavioral disturbance was noted in one of eight individuals following testosterone treatment. Similarly, 4 of 24 individuals ceased testosterone treatment due to increasing behavioral disturbance in a recent analysis in people with PWS (Kherra et al, 2021), whereas another analysis reported behavioral disturbance in one-third of individuals (Pellikaan et al, 2021). Few behavioral problems were attributed to testosterone treatment in a questionnaire of practitioners experienced in care of individuals with PWS (Eiholzer et al, 2021), and are not commonly reported in the literature following initiation of testosterone treatment (Noordam et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…PWS males have a normal mini-puberty during infancy with normally elevated luteinizing hormone (LH), follicle-stimulating hormone (FSH), and testosterone levels within the first few months of life [ 25 , 31 , 32 , 33 ]. After this mini-puberty, gonadotropins and testosterone decrease to pre-pubertal levels.…”
Section: Hormonal Features and Therapeutical Approachmentioning
confidence: 99%
“…After this mini-puberty, gonadotropins and testosterone decrease to pre-pubertal levels. Typically, males develop a delayed or incomplete puberty and consequently commonly become infertile in adulthood [ 25 , 31 , 32 , 33 ]. Cryptorchidism (either unilateral or bilateral) is almost universal in PWS males, ranging from 66% to 100% of newborns with PWS, and it requires orchiopexy to reposition the testicles in their correct anatomical location.…”
Section: Hormonal Features and Therapeutical Approachmentioning
confidence: 99%
See 2 more Smart Citations